1998
DOI: 10.1023/a:1008416911099
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum Rituximab (IDEC–C2B8) concentration and anti-tumor response in the treatment of recurrent low-grade or follicular non-Hodgkin’s lymphoma

Abstract: SummaryBackground; Monoclonal antibodies are being utilized for treatment of patients with low-grade non-Hodgkin's lymphoma as well as other cancers. Results from phase I and II clinical studies has shown that the chimeric monoclonal antibody Rituximab has minimal toxicity and significant therapeutic activity in low grade non-Hodgkin's lymphoma.Patients and methods; We have recently reported on a multicentre pivotal phase III clinical trial involving 166 patients with recurrent low-grade lymphoma who were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
340
8
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(373 citation statements)
references
References 22 publications
21
340
8
4
Order By: Relevance
“…7 Very few reports exist concerning its administration during pregnancy in humans. 8,9 Given rituximab's pharmacokinetic properties, 3,4,13 and as IgG is known to pass the placental barrier, its administration during pregnancy should consider the potential risk of B-cell depletion in the fetus and newborn. 2 In the two previous reports, both were in the setting of pregnant women with non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…7 Very few reports exist concerning its administration during pregnancy in humans. 8,9 Given rituximab's pharmacokinetic properties, 3,4,13 and as IgG is known to pass the placental barrier, its administration during pregnancy should consider the potential risk of B-cell depletion in the fetus and newborn. 2 In the two previous reports, both were in the setting of pregnant women with non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated b2-microglobulin, elevated LDH, bulky disease and age >60 years did not appear to impact response, implying that patients regarded as having a poor prognosis may respond to rituximab. Median rituximab serum levels were significantly higher in responders, compared with the non-responders (Berinstein et al, 1998). Mean serum antibody concentration was inversely correlated with the bulk of the disease and the number of circulating B cells, suggesting that patients with a higher tumor load might need higher doses or prolonged treatment, to achieve the necessary serum levels (Gordan et al, 2005).…”
Section: Rituximab In Flmentioning
confidence: 98%
“…Several arguments are in favor of this approach: the success of re-treatment or the strong correlation between rituximab plasma levels and RR (Berinstein et al, 1998). A recent randomized trial showed that adding maintenance doses of rituximab prolonged response duration (Ghielmini et al, 2004): 202 patients with newly diagnosed or refractory/relapsed FL were treated with standard rituximab (375 mg/m 2 weekly  4).…”
Section: Rituximab In Flmentioning
confidence: 99%
“…M ost of them stopped after only six treatments (6 weeks). This may be too short a treatment period for relevant therapy evaluation, especially when compared with rituximab therapy for malignant lymphomas (29,30). R esponse to rituximab therapy improved from 40% to 60% when the patients were treated during eight compared with four consecutive weeks.…”
Section: Discussionmentioning
confidence: 99%
“…R esponse to rituximab therapy improved from 40% to 60% when the patients were treated during eight compared with four consecutive weeks. It is possible that a prolonged course is needed, especially for patients with a large tumour bulk (29,30). R esponse evaluation for chemotherapy is normally scheduled after two or three courses given at threeweek intervals.…”
Section: Discussionmentioning
confidence: 99%